Peripheral lymphocyte populations in ovarian cancer patients and correlations with clinicopathological features - Shuang Ye; Wei Chen; Yuwei Zheng; Yutuan Wu; Libing Xiang; Teng Li; Bo Ping; Xiaoming Zhang; Huijuan Yang (BMC, 2022)
Highlights 1 Ovarian cancer patients have altered circulating lymphocyte profile 2 Low level of B cells might be related to disease aggressiveness, and it recovered after the removal of tumor.